Effects of preconditioning by nasal splint and mouth breathing on emergence delirium after functional endoscopic sinus surgery in Chinese adults: a study protocol for a randomised controlled trial. Issue 8 (26th August 2020) - Xu, Hongjiao; Li, Xiang; Yang, Bin; Shen, Zhenyuan; Li, Weiwen; Zhou, Yachun; Jiang, Jihong; Chen, Xia; Gu, Yuyu; Pei, Zhi; Li, Jinbao
Abstract : Introduction: Emergence delirium (ED) is a common adverse manifestation after general anaesthesia and may result in undesirable consequences. Its causes and mechanisms are diverse and complex, and it is still unavoidable in clinical work. There is a high incidence of ED after otorhinolaryngology surgery, which may result from the sudden loss of functional senses and discomfort of surgical organs. This study aims to test a non-invasive, non-drug treatment modality of nose clamping and mouth-breathing training before surgery to reduce ED. Methods and analysis: This prospective randomised controlled trial (RCT) will include 200 patients who undergo functional endoscopic sinus surgery (FESS) at Shanghai General Hospital, China. Study participants will be randomly assigned in two groups with a 1:1 ratio. The pretreatment group (P-group) will receive an intervention by nasal splint and mouth-breathing training before surgery, while the control group (C-group) will not receive any intervention; following which both groups will undergo FESS under general anaesthesia in accordance with the same anaesthesia scheme. After surgery, we will perform a single-blinded assessment of ED occurrence with stratification. IBM SPSS Statistics V.20 statistical software will be used for statistical analyses. A X 2 test will be used to compare the two groups, and t-tests will determine the statistical significance of continuous variables. Ethics and dissemination: This RCT was designed in accordance with the principles of the Declaration of Helsinki and has been approved by the Ethics Committee of Shanghai General Hospital, ID: 2019KY039.We expect to release the original data in February 2022 on the ResMan original data sharing platform (IPD sharing platform) of the China clinical trial registry, which can be viewed at the following website:http://www.medresman.org.cn/pub/cn/proj/projectshow.aspx?proj=6293 . Trial registration number: ChiCTR1900024925